Exploring the anti-diabetic potential of Antidesma alexiteria L.: In vitro GLUT-4 expression and molecular docking studies (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
GLUT-4, an insulin-regulated glucose transporter primarily located in skeletal muscle and adipose tissue, plays a crucial role in the insulin-stimulated uptake of glucose uptake. Impaired GLUT-4 transcription and translocation lead to insulin resistance and hyperglycemia.  Hence, this study investigates the role of bioactive compounds from plant sources using gene-level and in-silico interaction studies. In the present investigation, in-silico and in-vitro gene expression analysis of the GLUT-4 gene with acetone bark extract of A. alexiteria were conducted. GLUT-4 gene expression was analysed using 3T3-L1 adipose cells and insulin as standard. The results demonstrated a dose-dependent increase in GLUT-4 expression, with the highest expression observed at a 100μg/ml concentration. According to molecular docking research, the compound juziphine interacted with the catalytic residues Glu177 and Gly400 of the GLUT-4 protein, satisfying ADMET properties. The stability of protein-ligand complex was further validated by molecular dynamics simulations. The study suggested that the extract has insulin-mimetic properties, enhancing GLUT-4 expression, and that juziphine could serve as a promising anti-diabetic agent.